Immunomodulators in Combined Therapy of Patients with Chronic Hepatitis - M. G. Romantsov; T. V. Sologub; A. A. Shuldyakov; A. N. Bondarenko; A. L. Kovalenko (Антибиотики и Химиотерапия, 2020)
The efficacy of the use of triple schemes in combined therapy of chronic virus hepatitis was estimated and its safety was monitored. The problems of therapy of mixed hepatitis in drug addicts are discussed. Immunotropic agents, increasing the efficacy of the standard therapy of chronic affections of the liver, are suggested to be used as the third remedy in the combined therapy.